2005
DOI: 10.1128/mcb.25.8.3194-3208.2005
|View full text |Cite
|
Sign up to set email alerts
|

Novel Functions of the Phospholipase D2-Phox Homology Domain in Protein Kinase Cζ Activation

Abstract: It has been established that protein kinase C (PKC) participates in diverse signaling pathways and cellular functions in a wide variety of cells, exhibiting properties relevant to cellular survival and proliferation. Currently, however, the regulation mechanism of PKC remains elusive. Here, for the first time, we determine that phospholipase D2 (PLD2) enhances PKC activity through direct interaction in a lipase activity-independent manner. This interaction of the PLD2-Phox homology (PX) domain with the PKC-kin… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

1
29
0

Year Published

2005
2005
2018
2018

Publication Types

Select...
6
3

Relationship

1
8

Authors

Journals

citations
Cited by 36 publications
(30 citation statements)
references
References 67 publications
1
29
0
Order By: Relevance
“…Transfection was carried out with LipofectAMINE, according to the manufacturer's instructions. In HEK 293 cells, depletion of endogenous PLD2 was performed using small interference RNA (siRNA) for PLD2, as described previously (Kim et al, 2005). After starving the cells for 24 hours, they were incubated with 10 Ci [ 3 H]myristic acid for 3 hours.…”
Section: Liposome-binding Assaymentioning
confidence: 99%
“…Transfection was carried out with LipofectAMINE, according to the manufacturer's instructions. In HEK 293 cells, depletion of endogenous PLD2 was performed using small interference RNA (siRNA) for PLD2, as described previously (Kim et al, 2005). After starving the cells for 24 hours, they were incubated with 10 Ci [ 3 H]myristic acid for 3 hours.…”
Section: Liposome-binding Assaymentioning
confidence: 99%
“…The mechanisms for activation have been established for sequential phosphorylation, the recruiting of proper localization, and the exchanging of binding proteins (11). Growing evidence indicates that PKC family members play important roles in regulating cell survival and apoptosis (12)(13)(14)(15).…”
mentioning
confidence: 99%
“…PKC is insensitive to second messengers such as Ca 2ϩ and diacylglycerol. Thus, its activity is primarily regulated by protein-protein interaction and phosphorylation (11). The signal mechanisms for PKC activation include the PDK1-dependent (i.e.…”
mentioning
confidence: 99%
“…The signal transduction pathway infl uenced by FIC1 involves protein kinase C (PKC ), whereby PKC phosphorylates and activates FXR ( 7,25 ). The following studies were stimulated by the observation that phospholipase D2 has been shown to activate PKC ( 26 ).…”
Section: Pld2 Gain Of Functionmentioning
confidence: 99%